БОШЛАНҒИЧ ТАЪЛИМНИ ИНТЕГРАТИВ РИВОЖЛАНТИРИШ ЗАРУРИЯТИ - Ҳамзаев, Ҳ.Х. (SCIENCE and SOCIETY, 2021)
The article considers the necessity of the problem of development of primary education at the stage of innovative development of Uzbekistan on the basis of modern requirements.